Odpowiedzi

Najlepsza Odpowiedź!
2009-12-06T19:29:51+01:00
A) 7+(-2) = 7-2=5
b) (-0,8)-(-0,8)=-0,8+0,8=0
c) 7-(-2)=7+2=9
d) (-15)+(-3)=-15-3=-18
e) -(-3/4)+(-1/4)=3/4-1/4=1/2
f) -(-0,5)-(-1/2)=0,5+1/2=0,5+0,5=1
g) (-21)-(-15)=-21+15=6
h) -1,2-[-(-0,8)]=-1,2-0,8=-2
i) 24-(-15)+(-32)=24+15-32=39-32=7
2 4 2
2009-12-06T19:31:41+01:00
A) 7+(-2) = 7-2 = 5
b) (-0,8)-(-0,8) = -0,8 + 0,8 = 0
c) 7-(-2) = 7+2 = 9
d) (-15) + (-3) = -15 - 3 = -18
e) -(-3/4) + (-1/4) = 3/4 - 1/4 = 2/4
f) -(-0,5)-(-1/2) = 0,5 + 1/2 = 1
g) (-21)-(-15) = -21 + 15 = -6
h) -1,2-[-(-,8)] = -1,2 - 0,8 = -2
i) 24 - (-15) + (-32) = 24 + 15 - 32 = 39 - 32 = 7
1 5 1